Rancang Bangun Sistem Terdistribusi Dalam Meningkatkan Kualitas Layanan Kemahasiswaan - Siahaan, R. Fanry (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The development of the world of education at this time is classified as an advanced condition where not only can be seen from how the lecturer transfers the knowledge he has but also seen how the students are able to receive the knowledge provided. The field of education has also become a competition for this matter because there are more and more universities that are starting to provide good services to students and prospective students, with the intention of these universities being able to win the competition. The student service system in STMIK Pelita Nusantara is still manual, so the student services are still unsatisfactory. Data collection techniques in this study using a questionnaire, the model used for the construction of this distributed system is the waterfall method.